RELATIONSHIP OF CHILDREN NUMBERS AND THE APPLICATION EDUCATES SYSTEM IN THE VILLAGE KRIKILAN BAYAT SUB DISTRICT KLATEN REGENCY - Fika Intan Rizana; Feri Catur Yuliani; Sumantri . (STIKES DUTAGAMA KLATEN, 2014)
Background: The numbers of children many or few influenced with parents monitoring. The numbers of children which parents fate can influence educates system. Objectives: The aim of this research is to know the relationship between the children numbers and application educates system in the village Krikilan, Bayat sub district, Klaten regency. Research Methodology: Observasional research have an analytic quality with cross sectional design. This Research was done at November 2012 until August 2013, this research population is all of parents that have the children age 1-12 year in the village Krikilan, Bayat sub district, Klaten regency. There are 232 parents in that place. The sample collected technique is purposive sampling with 124 respondents which appropriate with inklusi criteria. Results: There are relationship between the numbers of children and the application education system in the village Krikilan Bayat sub district, Klaten regency, the percentage, p=0,001 (p<0,05), t count 3,260 (t count> 2,576) and the percentage r= 0,283. The parents which have the number of children >2 were applied otoritatif education system 18 (14,51%) and the number of children ≤2 tended to applied otoritatif education system 93 (75,00%). Conclusion: There is significant relationship between the children numbers and application educates system.